2013
DOI: 10.4258/hir.2013.19.4.278
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of National Patients Sample Analysis: Factors Affecting Mortality and Length of Stay of Organophosphate and Carbamate Poisoned Patients

Abstract: ObjectivesThis study considered whether there could be a change of mortality and length of stay as a result of inter-hospital transfer, clinical department, and size of hospital for patients with organophosphates and carbamates poisoning via National Patients Sample data of the year 2009, which was obtained from Health Insurance Review and Assessment Services (HIRA). The utility and representativeness of the HIRA data as the source of prognosis analysis in poisoned patients were also evaluated.MethodsOrganopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…Korea has a special system in which medical claims are made to the NHIS based on the resident registration number of each citizen [1314]. The health insurance claim data contains extensive information on the use of medical services, but it may be distorted in order to receive more compensation [15]. The scale of data also makes it difficult to identify the desired clinical data for analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Korea has a special system in which medical claims are made to the NHIS based on the resident registration number of each citizen [1314]. The health insurance claim data contains extensive information on the use of medical services, but it may be distorted in order to receive more compensation [15]. The scale of data also makes it difficult to identify the desired clinical data for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The scale of data also makes it difficult to identify the desired clinical data for analysis. HIRA-NIS-2009, verified as having national representativeness, was obtained from the health insurance claims of 2009 [171819], and it is being used in some studies [15]. Based on HIRA-NIS-2009, this study found that the incidence of IHCA was 2.46 per 1,000 admissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…За численними літературними даними [7,8,10], з початку масового застосу-вання пестициди залишаються важливими причинами отруєнь (особливо гострих) у багатьох країнах [3,9,21]. У свою чергу, за даними [7], у загальній структурі отру-єння пестицидними препаратами значна частка належить саме фосфорорганіч-ним сполукам (ФОС).…”
Section: вступunclassified
“…In addition, several factors including the route, duration, and frequency of exposure, contact with other pollutants, and compromised physiological condition (e.g. hepatic injury) may determine the degree of toxicity [7][8].…”
Section: Mode Of Action and Toxicologymentioning
confidence: 99%